2019
DOI: 10.1088/1674-4926/40/10/101301
|View full text |Cite
|
Sign up to set email alerts
|

III–V ternary nanowires on Si substrates: growth, characterization and device applications

Abstract: Over the past decades, the progress in the growth of materials which can be applied to cutting-edge technologies in the field of electronics, optoelectronics and energy harvesting has been remarkable. Among the various materials, group III-V semiconductors are of particular interest and have been widely investigated due to their excellent optical properties and high carrier mobility. However, the integration of III-V structures as light sources and numerous other optical components on Si, which is the foundati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 142 publications
(592 reference statements)
0
19
0
Order By: Relevance
“…III-V ternary nanowires (NWs) are particularly advantageous for the realization of optoelectronic devices, due to their direct band gap tunability. 1 This is widely achieved via controlling the distribution and composition of different elements, leading to controllable and tuneable emission in light-emitting applications. [2][3][4] An important phenomenon that is observed often in ternary NWs is the non-uniform compositional distribution, which is sensitive to various NW structural features.…”
mentioning
confidence: 99%
“…III-V ternary nanowires (NWs) are particularly advantageous for the realization of optoelectronic devices, due to their direct band gap tunability. 1 This is widely achieved via controlling the distribution and composition of different elements, leading to controllable and tuneable emission in light-emitting applications. [2][3][4] An important phenomenon that is observed often in ternary NWs is the non-uniform compositional distribution, which is sensitive to various NW structural features.…”
mentioning
confidence: 99%
“…GPA is a widely used method to map the strain field from high resolution TEM images based on Fourier‐space‐based data processing, [ 25–31 ] and has been applied for various materials. [ 32–42 ] However, GPA method can be difficult to be directly applied to STEM images, as low‐sampled STEM images often lose detailed information at atomic scale, in addition to other artifacts such as scanning noise and scanning distortions etc. Alternatively, STEM‐MF offers a possibility of strain measurement from STEM images.…”
Section: Theory and Developmentsmentioning
confidence: 99%
“…It is noted that a most intriguing phenomenon regarding epitaxial semiconductor NWs, which is encountered most frequently and reported very often, is that zinc-blende epitaxial NWs prefer to grow along <111> directions, [55,56] Conventionally, people assume that this phenomenon is attributed to the low surface energy of (111) surface. However, through a careful inspection of the literature, it is found that the current understandings on the surface energy could not lead us to the conclusive elucidation of this phenomenon as the surface energy measurements and calculations are based on merely a limited number of specific facets and directions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%